Implementation of Inclusive Education in Learning Process at Senior High School Malang City, Indonesia - Ediyanto Ediyanto; Aris Setiawan; Irvan Budi Handaka; Nurul Hidayati Rofiah; Suhendri Suhendri (The Center for Disability Studies and Services Brawijaya University, 2021)
One of the Public Senior High Schools in Malang has been implementing an inclusive education system since 2009. This School has been trying to serve children with special needs hitherto. In one of the inclusive schools in Malang city, the number of students with special needs (the academic year 2017-2018) is recorded in the school document of 9 students with special needs and 37 students with special services (have health problems). However, it is indicated that the learning process in class is not suitable for the type of student needs in the class. This study aims to investigate the learning process in these inclusive schools. The current research is explained in a descriptive qualitative method. As a result, schools do not make curriculum modifications that are compatible with inclusive education. This school only has one special guidance teacher, and only he has attended a training program in inclusive education. In addition, there are indications that the teacher's attitude toward students with special needs is negative. The indication can be seen from the teacher's efforts in implementing learning. The teacher still uses a classical learning system that is not modified. Thus, it is necessary to improve services for students' diversity in schools, increase the number of special tutors, include them in inclusive education training programs, and make curriculum modifications that are appropriate for students with special needs. The teacher is also indicated to have a negative attitude towards students with special needs in the classroom.